A Conglomerate of Pathology in Placental Disorders - Vahini, Gudeli; Renuka, I.V. (Annals of Pathology and Laboratory Medicine, 2018)
Background: There is a vast diversity in placental pathology and several factors contribute to this diversity. A detailed placental examination is mandatory to assess any disorder and predict fetal outcome. Aims and objectives: To study the placental pathology in various maternal, fetal and placental disorders and also the fetal outcome in these conditions. Materials and methods: A one and a half year prospective study of fifty consecutive placentae was done. A proforma was prepared with relevant clinical details. Maternal, fetal, placental risk factors were analyzed along with gross and microscopic lesions. Appropriate sections were taken from representative sites and Hematoxylin and eosin, Periodic acid Schiff stains were done. Results: Out of fifty cases of placentae studied, forty seven cases (94%) showed evidence of pathology associated with maternal, fetal and placental risk factors, either singly or in combination. Maternal risk factors were twenty five cases (50%) of which the highest percentage being pregnancy related (84 %). Grossly infarcts and retro placental hematomas were common findings. Histological features of accelerated maturation were lesions commonly seen in these cases. In cases where the fetal outcome was poor like in abortions, intrauterine fetal death and still births all (100%) placentae were abnormal. Conclusions: In this study high percentage of placentae showed evidence of pathology, the majority of which were associated with maternal, fetal or placental risk factors either singly or in combination. Those cases in which fetal outcome were poor all the placentae were abnormal. A careful examination of placentae is required as it is a clue for various diseases and to determine fetal outcome. Histopathological examination of both gross and microscopy proved to be valuable tools in determining placental pathology.